Reduction of Nitroarenes to Aromatic Amines with Sodium Borohydride in the Presence of Selenium and Actived Carbon - Ke Ying Cai; Ying Mei Zhou (Bulletin of Chemical Reaction Engineering & Catalysis, 2015)
A selenium and actived carbon (AC) catalyst has been applied for the selective reduction of nitroarenes to their corresponding amines respectively using sodium borohydride (NaBH4) as a reducing source un-der mild conditions. Under the optimized conditions, efficient and selective reduction of nitroarenes into the corresponding aromatic amines occurred over a recyclable selenium catalyst. The catalyst can be easily recovered after catalytic reaction and readily reused for 4 cycles with consistent activity hence reduces the cost of the catalyst. Copyright © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).